Cork oak (Quercus suber L.) seedlings acclimate to elevated - Vaz. M (2012)
Leaf gas-exchange, leaf and shoot anatomy, wood density and hydraulic conductivity were investigated in seedlings of Quercus suber L. grown for 15 months either at elevated (700 lmol mol-1) or normal (350 lmol mol-1) ambient atmospheric CO2 concentrations. Plants were grown in greenhouses in a controlled environment: relative humidity 50% (±5), temperature similar to external temperature and natural light conditions. Plants were supplied with nutrients and two water regimes (WW, well watered; WS, water stress). After 6 months exposure to CO2 enrichment an increase in photosynthetic rate, a decrease in stomatal conductance and a decrease in carbon isotope discrimination (D13C) were observed, along with enhanced growth and an increase in the number of branches and branch diameter. Over the same period, the shoot weight ratio increased, the root weight ratio decreased and the leaf weight ratio was unaffected. The specific leaf area increased due to an increase in total leaf thickness, mainly due to the palisade parenchyma and starch. However, after 9 and 15 months of elevated CO2 exposure, the above-mentioned physiological and morphological parameters appeared to be unaffected. Elevated CO2 did not promote changes in vessel lumen diameter, vessel frequency or wood density in stems grown in greenhouse conditions. As a consequence, xylem hydraulic efficiency remained unchanged. Likewise, xylem vulnerability to embolism was not modified by elevated CO2. In summary, elevated CO2 had no positive effect on the ecophysiological parameters or growth of water stressed plants.